Participatory Design Concepts for Autistic Children's Furniture Needs in the Behavioral Therapy Room using the ABA/Lovass Methods - Dwi Candra Purnamasari; Agatha Dinarah S.R; Sinta Sari M (Budapest International Research and Critics University, 2022)
The concept of designing behavioral therapy furniture for autistic children must consider the character of autistic children and the therapeutic methods used. The physical environment that meets the needs of autistic children, especially furniture with adapted materials and shapes, greatly influences therapeutic activities. This study aims to implement the participatory design concepts as the basis for designing furniture for autistic children's therapy rooms. The participatory design concept is implemented in the materials and forms of furniture needs tailored to the needs of autistic children. Therefore, designing furniture can support the needs of autistic children in therapy.